Theoretical and experimental researches for defining the loads during explosive burning of air-gas-dusty mixtures - Kakenov, K.S. (Publishing House of the KarSU named after E.A.Buketov, 2011)
The article primary results theoretical and experimental researches for defining the loads during explosive burning of air-gas-dusty mixtures. The rated equations for definition of the maximal load arising at explosion of a coal dust in industrial facility are resulted. The possibility of carrying out of analogy is marked by explosions of a coal dust and air-gas mixtures. Influence of various factors on speed propagation of a flame is analyzed at explosion. The rightness of the choosen theoretical premises was confirmed by the experimental researches.
Keywords: explosion; explosive burning; air-gas-dusty mixtures; coal dust; air-gas mixtures